Hubungan Dukungan Suami Dan Tingkat Kecemasan Dengan Kesiapan Ibu Hamil Usia 17-19 Tahun Dalam Menghadapi Persalinan - Maryono, Maryono; Afrina, Rina; Ghanesia Istiani , Hari (The Health Researcher's Journal, 2024)
Childbirth readiness is the process of planning birth and anticipating actions to prevent complications. Teenage pregnant women (<20 years) are at risk because at that age their reproductive and mental functions are not yet mature. This study aims to analyze the relationship between husband's support and childbirth readiness among teenage pregnant women in the work area of the East Bogor Community Health Center. This research uses accidental samples by taking cases or respondents who happen to exist or are available in a place according to the research context. The sample size was 50 teenage pregnant women using total sampling. Data were obtained using the husband's support questionnaire (validity: 0,410-0,695 and reliability: 0.964), anxiety level (validity: 0.671-0.902 and reliability: 0.808) and labor readiness questionnaire (validity: 0.700-0.896 and reliability: 0.0602). Data analysis used the chi-square test. The research results showed that there was a relationship between husband's support and childbirth readiness (p-value = 0.006) and there was a relationship between anxiety level and childbirth readiness (p-value = 0.000). This research shows that the higher the husband's support received by pregnant women, the higher the readiness for childbirth. Teenage pregnant women who have good husband support will prepare a more mature birth plan and program, so that the pregnant woman's birth goes smoothly and provides safety for the mother and fetus.